2016
DOI: 10.3233/bmr-150614
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the abductors in patients with hip osteoarthritis: Systematic review and meta-analysis

Abstract: Hip abductor strength is reduced in OA patients when compared to healthy controls and to the unaffected limb. Data on muscle size and activity is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Muscle size is associated with strength 12,13 , yet previous systematic reviews of hip pathology have found little or no differences in hip muscle size compared with matched peers 2,3 . The absence of differences in hip muscle size despite differences in strength could have several explanations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Muscle size is associated with strength 12,13 , yet previous systematic reviews of hip pathology have found little or no differences in hip muscle size compared with matched peers 2,3 . The absence of differences in hip muscle size despite differences in strength could have several explanations.…”
Section: Introductionmentioning
confidence: 96%
“…Muscle size and composition have previously been evaluated in advanced OA 2,3 . No review of the literature has considered muscle changes with respect to different grades of pathology or across the spectrum of articular hip pathology that are purported to precede and contribute to the pathogenesis of OA.…”
Section: Introductionmentioning
confidence: 99%
“…The gluteus medius (GMed) and minimus (GMin) function as hip abductors and are considered to be the major stabilisers at the hip joint 8 . Hip abductor strength deficits are commonly seen in hip OA patients 9 . Weakness in muscle can be manifested as either a reduction in muscle size or muscle activity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In their systematic review, Marshall et al 25 concluded that hip abductor muscle size is similar between those with hip OA and asymptomatic participants. With close assessment of the individual studies cited in their review and another recently published study, there is some evidence to suggest that findings may be affected by the participant’s age, stage of disease, or symptom duration.…”
Section: Discussionmentioning
confidence: 99%
“…With close assessment of the individual studies cited in their review and another recently published study, there is some evidence to suggest that findings may be affected by the participant’s age, stage of disease, or symptom duration. 14, 25, 38 When comparing symptomatic limbs in those with hip OA to asymptomatic participants, Zacharias et al 38 found that individuals with advanced OA (K/L 3), had significantly smaller GMax, GMed, and GMin. However, those with mild hip OA (K/L 2), had similar muscle volume to that of asymptomatic people.…”
Section: Discussionmentioning
confidence: 99%